PROBLEMATIKA PARA STAKEHOLDER DALAM TRANSAKSI AFILIASI DI PERUSAHAAAN GRUP - Andre Febriansyah (2023)
A business group is an organization consisting of multiple companies that have economic and legal relationships. In a business group, subsidiary companies engage in affiliate transactions with the Holding Company or with other subsidiaries under the control of the Holding Company. Affiliate transactions can provide benefits to the business group, such as improving efficiency, reducing costs, or strengthening market position. However, affiliate transactions can also pose legal problems, especially for the stakeholders of subsidiary companies who may be disadvantaged by these transactions. The development of affiliate transactions within business groups and the complexity of conglomerate businesses in Indonesia are not specifically regulated under the Republic of Indonesia Law Number 40 Year 2007 concerning Limited Liability Companies (Company Law). This creates legal loopholes that holding companies can exploit to avoid legal responsibility in affiliate transactions between companies. This research aims to analyze the issues faced by stakeholders of subsidiary companies in affiliate transactions within business groups. The research methodology used is normative juridical with a case study approach and a statutory approach. The research findings indicate that holding companies can be held accountable for the risks of affiliate transactions in subsidiary companies if there is evidence of control in those transactions. Holding companies share the responsibility of conducting affiliate transactions with subsidiary companies in a fair, transparent, and respectful manner towards the rights of stakeholders. To strengthen legal protection and certainty regarding the responsibility of holding companies towards stakeholders for the impacts of affiliate transactions, amendments to the Company Law are needed, including definitions, transparency, protection, supervision, and sanctions related to the responsibility of holding companies in affiliate transactions.